Information Literacy and Training Needs of Nursing Managers for Evidence-Based Practice - J Farokhzadian; L Ahmadian; R Khajouei; P Mangolian Shahrbabaki (Iran University of Medical Sciences, 2016)
Abstract Background & Aims: Nursing managers play an important role in the implementation of evidence-based practice (EBP) in clinical settings. Hence, their information literacy is an important prerequisite for providing this service. The objectives of this study were to examine information literacy of nursing managers  and to determine their training needs in the context of EBP. Materials & Methods: This descriptive and cross-sectional study was conducted in four hospitals affiliated with Kerman University of Medical Sciences in 2014. Data were collected from 70 nursing managers of these hospitals using a questionnaire. Data were analyzed in SPSS 16 using descriptive (percentage, mean, standard deviation) and analytic statistics (t-test, analysis of variance). Results: The participants used more printed and human resources (1.97±0.97) than electronic resources to seek information. The mean scores of using different search features in online databases and search engines was very low (1.78±1.04). A small percentage of participants were aware of the purpose and functions of Boolean and Proximity operators, so that only 17% of them chose the most appropriate option to search information from a database. Educational need assessment showed that participants demand for training in different fields of EBP was at a medium level (3.89±0.97). Conclusion: Nursing managers do not possess required skills to search and retrieve information from electronic resources and they use these up-to-date resources scarcely. Because of this, they can not guide and encourage nursing staffs to use the required knowledge and skills, as well as innovative techniques to provide a high quality care. It is recommended that future studies evaluate the role of clinical librarians, medical informaticians and clinical nurse educators for promoting information literacy of healthcare providers.